(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
Radio, cinema, television, the internet… The mass media have evolved over the course of time, yet what remains unchanged has been governments ’or lobbies’ interest in keeping them under their control, with a view to influencing society’s thinking and ideology. In war and any other periods of conflict, this control over information has been a matter of national concern. In fact, during the Great War, despite limited media outreach capability when compared with the immediacy, capacity and penetration of today, governments realised the huge benefit that they could obtain from their use for propaganda purposes to support the war effort. One of the simplest means was the graphic publication, which may encompass comics, daily or regular strips, cartoons and posters. The objectives of this article are twofold: firstly, to analyse the real impact of graphic publications on society during World War I; and lastly, to provide a different viewpoint for the study of any war through its visual propaganda.